Inovasi Strategi Pemasaran Pariwisata Dalam Meningkatkan Kunjungan Wisatawan di Kabupaten Siak - Paula Chandra (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The purpose of this study is to ascertain how innovative tourism marketing techniques may boost visitor numbers in Siak Regency. The Siak Regency Tourism Office and Siak Sri Indrapura's tourist attractions carried out this study. A qualitative method was used to gather study data from 114 employees. The descriptive analytic approach was employed in this study to address research issues pertaining to innovative tourist marketing tactics in Siak Regency. According to the study's findings, the Siak Regency Tourism Office has implemented a tourism marketing innovation strategy that aims to increase visitor visits. This strategy relies on three of the five components of the current tourism marketing innovation strategy. A plan for product, service, and value-added innovation has been put into action by the Siak Regency Tourism Office. However, the Siak Regency Tourism Office has not yet put the elements of the process innovation plan and product quality innovation strategy into practice. Inadequate funding availability and low community involvement in Siak Regency's tourist development are the main challenges the Siak Regency tourist Office is now facing when putting innovative methods into practice.